Danone Relation with the Stakeholcer in Multi-Party Partnership Project (Case study in Nanggerang Village) - Febrian, Muhammad Ichsan; Rudito, Bambang (Journal of Business and Management, 2013)
Indonesia is one of developing countries in the world. Developing countries usually face some common challenge that is economic crisis, the lack of education among poor communities, even environmental problems. Especially undeveloped area Nanggerang village, Sukabumi, West Java, Indonesia. The lack of water system and sanitation became a vital problem for Nanggerang village. This problem made quite impacts for Nanggerang village community in their daily life, economic and environmental condition. The problem is in the village nanggerang extremely vital, due to the absence of supporting clean water in the village. Therefore, PT. Danone Aqua CSR held to resolve the problems in the village. PT. Danone Aqua is responsible for water supply in the village limits nanggerang because it is located in close proximity to the company's spring water. With the passage of these CSR activities, PT. Danone Aqua involving many stakeholders, which he called the Multi-party partnership program. By involving the central government as PU, local governments, NGOs namely YPCII, and also with local residents. this is where the problem occurs I call with a problem in community relations.Â Keywords: Multi-Party Partnership, YPCII, NGOs, Pemda, PU, Wash Program